Fatigue behaviour of nanoclay reinforced epoxy resin composites - Ferreira, J. A. M. (2013)
Nanoparticle filling is a feasible way to increase the mechanical properties of polymer matrices. Abundant research work has been published in the last number of years concerning the enhancement of the mechanical properties of nanoparticle filled polymers, but only a reduced number of studies have been done focusing on the fatigue behaviour. This work analyses the influence of nanoclay reinforcement and water presence on the fatigue behaviour of epoxy matrices. The nanoparticles were dispersed into the epoxy resin using a direct mixing method. The dispersion and exfoliation of nanoparticles was characterised by X-ray diffraction (XRD) and transmission electron microscopy (TEM). Fatigue strength decreased with the nanoclay incorporation into the matrix. Fatigue life of nanoclay filled composites was significantly reduced by the notch effect and by the immersion in water.